Identifying natural playscape elements in a neighbourhood park: a case study of Kuantan, Malaysia - Ismail, Nor Atiah; Safiullah, Shaharuddin; Mohd Yunus, Mohd Yazid; Utaberta, Nangkula; Ismail, Sumarni (American-Eurasian Network for Scientific Information, 2015)
Nowadays playground looks stereotype because it is relies on manufactured products. This type of playground is more focusing on physical activity but less in generating social skills and cognitive development. Many believe that understanding of children‟s active living in their relationship to build environment is possible through concept of affordance. Through this concept, it gives understanding impact of the physical environment associated to the children by generate physiological and psychological. This paper is to identify for natural playground area that can enhance children‟s play experience and their outdoor exploratory learning and investigate of children preference for natural playscape elements as part of their play experience. It is important to design and develop children‟s playscape that can stimulate their physical, social skills and cognitive development